Mjesto simultanizma u Nabokovljevoj i Pasternakovoj estetici - Medarić, Magdalena (Array, 2000)
This paper deals with a certain typological analogy between two Russian writers which may be seen as a result of their commitment to the contemporary idea of time. Simultaneity was a global idea at the begining of the century, also an artistic concept and a programe thet affected many visual artists, poets and prose writers, especially in the early avant-garde (1910-1914). In literary scholarship it has been fixed as a literary term (Simultaneitat, simul'tanizm, etc) meaning artistic devices to convey the effect of different, often semantically disparat, objects or events distant from each other in space, but happening simultaneusly, e.i. in the same physical time.